2015
DOI: 10.1371/journal.pone.0130164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Maturation Systems on Bovine Oocyte Quality, Plasma Membrane Phospholipid Composition and Resistance to Vitrification and Warming

Abstract: The objective of this study was to evaluate the effects of different maturation systems on oocyte resistance after vitrification and on the phospholipid profile of the oocyte plasma membrane (PM). Four different maturation systems were tested: 1) in vitro maturation using immature oocytes aspirated from slaughterhouse ovaries (CONT; n = 136); 2) in vitro maturation using immature oocytes obtained by ovum pick-up (OPU) from unstimulated heifers (IMA; n = 433); 3) in vitro maturation using immature oocytes obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
3
22
0
2
Order By: Relevance
“…The changes in the lipid structural composition of the membranes, which are not possible to detect using staining procedures, are readily detected by matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) [ 70 ], and the understanding of lipid membranes composition is fundamental to address the difficulties of post cryopreservation embryo survival. Additionally, the oocyte quality [ 71 ], season of the year [ 72 ] culture conditions [ 46 , 52 , 73 ], cryopreservation method [ 74 ], as well as interactions between these factors [ 75 ], may affect embryo cryotolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the lipid structural composition of the membranes, which are not possible to detect using staining procedures, are readily detected by matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) [ 70 ], and the understanding of lipid membranes composition is fundamental to address the difficulties of post cryopreservation embryo survival. Additionally, the oocyte quality [ 71 ], season of the year [ 72 ] culture conditions [ 46 , 52 , 73 ], cryopreservation method [ 74 ], as well as interactions between these factors [ 75 ], may affect embryo cryotolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cattle, no studies have currently reported the production of calves from follicles at stages earlier than preantral follicles. Previous studies described bovine calves derived from IVG oocytes that originated from OCGCs in early antral follicles [5,6,7]; however, their developmental competence to transferable embryos was lower than the competence of in vivo matured oocytes [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we suggest that incubation might be the source of the differences between COCs and later stages. Mass-spectrometry study evidence that lipid content may differ in fresh and in vitro cultured oocytes and embryos (68,69). These observations are also in agreement with the different biological properties of in vitro and in vivo matured oocytes (70).…”
Section: Discussionmentioning
confidence: 99%